The MMR Vaccine and Autism - DeStefano, Frank (Annu Rev Virol, 2019)
Autism is a developmental disability that can cause significant social, communication, and behavioral challenges. A report published in 1998, but subsequently retracted by the journal, suggested that measles, mumps, and rubella (MMR) vaccine causes autism. However, autism is a neurodevelopmental condition that has a strong genetic component with genesis before one year of age, when MMR vaccine is typically administered. Several epidemiologic studies have not found an association between MMR vaccination and autism, including a study that found that MMR vaccine was not associated with an increased risk of autism even among high-risk children whose older siblings had autism. Despite strong evidence of its safety, some parents are still hesitant to accept MMR vaccination of their children. Decreasing acceptance of MMR vaccination has led to outbreaks or resurgence of measles. Health-care providers have a vital role in maintaining confidence in vaccination and preventing suffering, disability, and death from measles and other vaccine-preventable diseases.